Trade Secret Protection of Traditional Chinese Medicine Technology in the New Era: Internal Logic, Realistic Dilemma and Optimization Path (Lex localis - Journal of Local Self-Government, 2025)
Abstract: In the process of patenting traditional Chinese medicine (TCM) technology, the patent system has gradually deviated from its original purpose and philosophy of TCM. This has resulted in a majority of TCM technical information being protected as trade secrets in practice, rather than through patents. Protecting TCM technical information as trade secrets can be highly appropriate. However, due to the need for technological innovation and protecting public interest, there is an inherent conflict between information disclosure and confidentiality in trade secret protection of TCM technology. Moreover, when TCM technical information that was originally a trade secret gets reclassified as a state secret, the boundaries between private and public rights become blurred. The space for private rights protection gets encroached upon as public law protection becomes more generalized, leading to issues of rent-seeking behavior. To address these problems and find an optimal approach to protecting TCM technology trade secrets, several measures can be taken: 1) Adhere to the principle of balancing stakeholder interests 2) Reasonably divide the scope of TCM technical information disclosure based on different disclosure needs and purposes 3) Use various means to clarify the boundaries between trade secrets and state secrets in TCM 4) Limit the scope of TCM state secret protection to improve accuracy in determining TCM state secrets and curb the trend of over-generalizing state secret protection in TCM.